2015
DOI: 10.1016/j.apsusc.2014.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Structure characterization and strain relief analysis in CVD growth of boron phosphide on silicon carbide

Abstract: a b s t r a c tBoron phosphide (BP) is a material of interest for development of a high-efficiency solid-state thermal neutron detector. For a thick film-based device, microstructure evolution is key to the engineering of material synthesis. Here, we report epitaxial BP films grown on silicon carbide with vicinal steps and provide a detailed analysis of the microstructure evolution and strain relief. The BP film is epitaxial in the near-interface region but deviates from epitaxial growth as the film develops. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Previous theoretical work has shown that graphene-like BP monolayer is semiconductor with a direct band gap ranging from 0.81 eV to 1.82 eV, which may be used to fabricate electronic device in nanoscale [20, 32−36]. Experimentally, BP films have been synthesized on silicon carbide by CVD method [37]. In this work, we show that BP monolayer has a graphene-like global minimum structure.…”
Section: Introductionmentioning
confidence: 63%
“…Previous theoretical work has shown that graphene-like BP monolayer is semiconductor with a direct band gap ranging from 0.81 eV to 1.82 eV, which may be used to fabricate electronic device in nanoscale [20, 32−36]. Experimentally, BP films have been synthesized on silicon carbide by CVD method [37]. In this work, we show that BP monolayer has a graphene-like global minimum structure.…”
Section: Introductionmentioning
confidence: 63%
“…SiC is also now widely available. Although there have been several reports of BP growth on SiC [12,13,14,15], Lu, et al [11] have provided the only report of B 12 P 2 growth on SiC where BBr 3 and PBr 3 in H 2 was used to deposit B 12 P 2 on 6H-SiC. However, the maturity, quality and availability of bulk SiC substrates has greatly improved in the ten years since Lu et al's study.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)], belong to the group of III-V semiconductors, having been of great importance for electronic and optoelectronic applications [1][2][3][4][5][6][7][8]. BAs has recently received special attention, as it has been predicted from the first-principles approach to have a remarkably high value of thermal conductivity (κ) at room temperature (2240 W m −1 K −1 ), comparable to that of diamond [9].…”
Section: Introductionmentioning
confidence: 99%